Raw data from SeaExplorer SEA070 in the Amundsen Sea, 2022, as part of the TARSAN and ARTEMIS deployments on cruise NBP2202. - Queste, Bastien (University of Gothenburg, 2026)
This dataset contains raw Level-0 glider observations from SeaExplorer SEA070 (“Scratch”) collected in the Amundsen Sea during the NBP2202 expedition in early 2022. It forms part of the TARSAN and ARTEMIS efforts associated with the International Thwaites Glacier Collaboration. TARSAN focused on how atmosphere–ice–ocean interactions influence the Thwaites and Dotson ice shelves, using gliders, ship surveys, AUVs, moorings, and CTDs to characterize ocean conditions on the continental shelf and beneath ice shelves. ARTEMIS complemented that work by adding biogeochemical observations, especially from autonomous platforms, to investigate how West Antarctic Ice Sheet melt affects ecosystem structure and regional carbon cycling.

SEA070 data is provided in raw csv format as a timeseries-style, spanning about mid-January to mid-February 2022 in the eastern Amundsen Sea near 72.2–72.4°S, 117.9–117.3°W. The dataset includes core hydrography from an RBR Legato CTD (temperature, conductivity, salinity, pressure), dissolved oxygen from an RBR Coda sensor, nitrate from a Sea-Bird Deep SUNA, and optical measurements from a WET Labs ECO Puck FLBBCD (chlorophyll, CDOM, backscatter). All data is uncalibrated.

Note that there was a severe CTD electrical noise issue affecting conductivity, absolute values are OK but the data is incredibly noisy.

Processed data set is accessed here: https://doi.org/10.5281/zenodo.19219996
Keywords: Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser